#### Answer

$t^2+6t+9$

#### Work Step by Step

$x^m \cdot x^n = x^{m+n}$
Use the rule above to obtain:
$=(t+3)^{7+(-5)}
\\=(t+3)^{2}$
Use the formula $(a+b)^2=a^2+2ab+b^2$, where $a=t$ and $b=3$, to obtain:
$=t^2 + 2(t)(3) + 3^2
\\=t^2+6t+9$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$t^2+6t+9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.